2003
DOI: 10.1080/08830180305216
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Induction of Apoptosis by Intrinsic and Extrinsic Mechanisms

Abstract: It is now firmly established that apoptosis is an important mechanism of influenza virus-induced cell death both in vivo and in vitro. Data are predominantly from experiments with influenza A virus and in vitro experimental systems. Multiple influenza virus factors have been identified that can activate intrinsic or extrinsic apoptotic induction pathways. Currently there is no evidence for influenza virus directly accessing the apoptosis execution factors. The best-studied influenza virus inducers of apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 87 publications
4
85
0
Order By: Relevance
“…The virus predominantly infects and damage epithelial cells of respiratory tract and often results in cell death with apoptotic characteristics. Infection of epithelial cells and lymphocytes has been shown to induce apoptosis in vitro [6,14,17,24]. Infection with virulent influenza (H5N1) virus was also shown to induce lymphopenia and lymphocyte apoptosis in vivo [8,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus predominantly infects and damage epithelial cells of respiratory tract and often results in cell death with apoptotic characteristics. Infection of epithelial cells and lymphocytes has been shown to induce apoptosis in vitro [6,14,17,24]. Infection with virulent influenza (H5N1) virus was also shown to induce lymphopenia and lymphocyte apoptosis in vivo [8,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic cells undergo several complex morphological changes, including development of fragmented nuclei, extensive chromatin condensation and loss of cell volume. Recent studies have indicated that many viruses carry genes, like NS1 and NA, which directly influence the apoptotic ability of their host cell thus changing the view about significance of apoptosis in determining the outcome of virus infections [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 shows the amino acid sequence (Panel A) and in silico analysis of p13's structure (Panel B, ProtScale software, [5]) indicating that the N-terminus of the protein includes an amphipathic a-helix (residues 20-35) and a transmembrane region (residues [30][31][32][33][34][35][36][37][38][39][40]. These predictions are supported by circular dichroism analysis of a synthetic peptide corresponding to residues 9-41 (p13 ) which folds into an a-helix when exposed to membrane-like environments (e.g.…”
Section: Amino Acid Sequence and Structural Features Of Htlv-1 P13mentioning
confidence: 99%
“…Segments A-D of the protein represent, respectively, the amphipathic a-helical domain, the transmembrane domain, the hinge region and the C-terminal beta sheet hairpin. Panel C also shows a more detailed helical wheel model of the amphipathic a-helical domain of p13 (amino acids [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Panel C does not indicate the matrix and intermembrane space faces of the inner membrane, as the topology of p13 has not been defined.…”
Section: Amino Acid Sequence and Structural Features Of Htlv-1 P13mentioning
confidence: 99%
See 1 more Smart Citation